Fifty years of communism in Russia. Ed. with an introd. by M.M. Drachkovitch. With contribs of B.D. Wolfe, L. Schapiro, G. Warren Nutter [a.o.] (The Pennsylvania State University Press, 1968)
A publication of the Hoover Institution on War, Revolution and Peace.